Peran Orang Tua Mengatasi Sibling Rivalri - sunarti; Padhila, Nur Ilah; Ramli, Rahmawati (Window of Community Dedication Journal, 2023)
Abstract  An individual aged zero to eighteen years of growth and development who has special needs, including physical, psychological, social and spiritual needs, is often referred to as a child. During this period, it will be easier for children to learn and understand new things. Some children grow up with their siblings. The existence of siblings often gives rise to feelings of jealousy, anger and fear in children, these feelings will give rise to sibling rivalry. Sibling rivalry can have various undesirable impacts on both the child's psychology and the health of his or her siblings. The impact of sibling rivalry that is not resolved during childhood can trigger violent behavior in the future. Partner Problems: Lack of parental knowledge about how to deal with sibling rivalry in toddlers, Lack of parental awareness about implementing appropriate parenting patterns for toddlers who are at risk of sibling rivalry and Lack of public education regarding sibling rivalry in toddlers by local health workers. The results of the implementation of the activities that have been carried out show that family knowledge has changed from not knowing to knowing where out of 27 participants showed good knowledge of the patient's family after being given counseling as many as 21 (77.7%) and there were still 6 (22.3%) parents who less knowledgeable. This is because 6 of these 27 people are elderly and do not really understand the Indonesian language used when health education is carried out, but the majority of the counseling participants understand and are enthusiastic about following the counseling until it is finished.